Ecological security in risk society - Tatyana V., Mishatkina (Journal of the Belarusian State University. Ecology, 2021)
The current situation in the risk society characterised by the new realities (from the global climate change to the pandemic penetration of a new virus in the human body) has brought to light the need to turn to a new paradigm of posthumanism, i.e. supplementing the unequivocal optimistic orientation on sustainable development with a more pessimistic, but also more topical and realistic, survival strategy aligned with extreme ethics, a new for ecological security in risk society.